2003
DOI: 10.1001/jama.289.22.2958
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Mortality in Weekend vs Weekday Births

Abstract: Context Increases in neonatal mortality for infants born on the weekend were last noted several decades ago. Although the current health care environment has raised concern about the adequacy of weekend care, there have been no contemporary evaluations of daily patterns of births, obstetric intervention, and case mix-adjusted neonatal mortality. Objective To compare the neonatal mortality of infants born on weekdays and weekends. Design, Setting, and Participants Case series of 1 615 041 live births (weight Ն5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
110
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(123 citation statements)
references
References 13 publications
11
110
1
1
Order By: Relevance
“…18, 19 Bell and Redelmeier in 2001 13 and Cram et al in 2004 20 reported that the case fatality risk of AMI was higher in patients admitted on weekends than in those admitted on weekdays, as it was in this current study. However, in the earlier studies, the differences in the case fatality rate became statistically insignificant after adjusting for age, sex, and severity of AMI.…”
Section: Discussionsupporting
confidence: 59%
“…18, 19 Bell and Redelmeier in 2001 13 and Cram et al in 2004 20 reported that the case fatality risk of AMI was higher in patients admitted on weekends than in those admitted on weekdays, as it was in this current study. However, in the earlier studies, the differences in the case fatality rate became statistically insignificant after adjusting for age, sex, and severity of AMI.…”
Section: Discussionsupporting
confidence: 59%
“…These results are also consistent with a recent study of neonatal mortality rates that used multivariate logistic regression to adjust for the severity of illness and the case mixture. 24 Although earlier neonatal studies noted higher weekend mortality rates, those analyses likely did not adjust adequately for potential confounders. 4,[6][7][8] Interestingly, the lack of a weekend effect in the current study and the recent neonatal study 24 differs from the results observed by Bell and Redelmeier, 1 who evaluated mortality rates among adult emergency admissions between 1988 and 1997 in Ontario, Canada.…”
Section: Discussionmentioning
confidence: 98%
“…24 Although earlier neonatal studies noted higher weekend mortality rates, those analyses likely did not adjust adequately for potential confounders. 4,[6][7][8] Interestingly, the lack of a weekend effect in the current study and the recent neonatal study 24 differs from the results observed by Bell and Redelmeier, 1 who evaluated mortality rates among adult emergency admissions between 1988 and 1997 in Ontario, Canada. The difference between these findings may represent differences between adult and pediatric patient populations or a distinction between the structure or processes of health care for adult versus pediatric patients.…”
Section: Discussionmentioning
confidence: 98%
“…3,[6][7][8]11,[13][14][15][16]23,29,31,34 These databases could potentially include coding errors, usually originating from the hospital level, 9 although it seems likely that such errors would be consistent across the entire database rather than isolated to the weekend admissions. In addition, the database contains discharge records, which include discharges to other hospitals.…”
mentioning
confidence: 99%